2013
DOI: 10.1007/s00401-013-1160-3
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of human α-synuclein from the olfactory bulb to interconnected brain regions in mice

Abstract: α-Synuclein (α-syn) is a protein prevalent in neural tissue and known to undergo axonal transport. Intracellular α-syn aggregates are a hallmark of Parkinson’s disease (PD). Braak and collaborators have suggested that in people who are destined to eventually develop PD, α-syn aggregate pathology progresses following a stereotypic pattern, starting in the olfactory bulb (OB) and the gut. α-Synuclein aggregates are postulated to spread to interconnected brain regions over several years. Thus, propagation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
217
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 245 publications
(261 citation statements)
references
References 61 publications
28
217
0
4
Order By: Relevance
“…This finding is similar to another study of intranasal administration of αS (25). Recently, Rey et al (47) have shown that injection of exogenous monomeric or aggregated αS in the mouse olfactory bulb can result in the transport to neurons of neuroanatomically connected brain regions, but the injected proteins had a short half-life (less than 72 h) and no induction of αS pathology was observed (47). Thus, it appears that the higher endogenous levels of αS in primed animals greatly accentuate the experimental peripheral induction of αS pathology.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is similar to another study of intranasal administration of αS (25). Recently, Rey et al (47) have shown that injection of exogenous monomeric or aggregated αS in the mouse olfactory bulb can result in the transport to neurons of neuroanatomically connected brain regions, but the injected proteins had a short half-life (less than 72 h) and no induction of αS pathology was observed (47). Thus, it appears that the higher endogenous levels of αS in primed animals greatly accentuate the experimental peripheral induction of αS pathology.…”
Section: Discussionsupporting
confidence: 91%
“…Comparable to prion diseases, in which the pathological prion protein propagates by a seeding/nucleation polymerization process and is transferred from cell to cell, stereotypic spread has been observed in e.g. synucleopathies and Alzheimer's disease [21][22][23][24]. For in vitro and in vivo studies and especially for the examination of the neuropathologically characteristic misfolded, oligomerized and aggregated proteins discrimination between normal and aberrant forms is essential.…”
Section: Discussionmentioning
confidence: 99%
“…other neurodegenerative disorders (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). α-Synuclein is largely cytosolic, but readily binds to membranes, and associates with synaptic vesicles in the presynaptic terminal (22,23).…”
Section: α-Synuclein Multimerizes On Phospholipid Surfaces In An Antimentioning
confidence: 99%
“…Moreover, α-synuclein is a major component of intracellular protein aggregates called Lewy bodies, which are pathological hallmarks of neurodegenerative disorders such as PD, Lewy body dementia, and multiple system atrophy (11)(12)(13)(14). Strikingly, neurotoxic α-synuclein aggregates propagate between neurons during neurodegeneration, suggesting that such α-synuclein aggregates are not only intrinsically neurotoxic but also nucleate additional fibrillization (15)(16)(17)(18).…”
mentioning
confidence: 99%